2020
DOI: 10.1530/ec-20-0193
|View full text |Cite
|
Sign up to set email alerts
|

Pleural effusion as a novel prognostic factor in metastatic thyroid carcinoma

Abstract: Objective: To identify novel prognostic risk factors and compare them with other known prognostic risk factors in follicular cell derived thyroid carcinoma (FDTC) with distant metastases. Methods: A retrospective review was conducted of adult patients with metastatic FDTC seen at a tertiary care center between January 1990 and December 2010. A 15-year Kaplan-Meier survival estimate was created for overall survival (OS) and cancer-specific survival (CSS). Hazard ratios (HR) and P values from Cox proportional h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…As expected, the presence of a malignant pleural effusion in a patient with differentiated thyroid carcinoma denotes an extremely poor prognosis, 14 and patients usually die within a year of the onset of pleural effusion. In our patient cohort, the median survival was approximately 8.5 months.…”
Section: Discussionsupporting
confidence: 57%
“…As expected, the presence of a malignant pleural effusion in a patient with differentiated thyroid carcinoma denotes an extremely poor prognosis, 14 and patients usually die within a year of the onset of pleural effusion. In our patient cohort, the median survival was approximately 8.5 months.…”
Section: Discussionsupporting
confidence: 57%
“…A previous study reported that patients with a pleural effusion survived a duration of 0.1-82.8 months and pleural effusion was the prognostic factor among patients with metastatic thyroid cancer [20]. Furthermore, the events of pleural effusion may predict bad prognosis during lenvatinib treatment [21].…”
Section: Discussionmentioning
confidence: 99%
“…Ten months later, after discovering the metastasis, the patient’s medical condition progressed and he passed away, thus authenticating that such presentation of PTC was found to be correlated with poor prognosis and shortened overall survival [ 31 , 43 ]. A retrospective report of patients with cancer with metastatic follicular-cell-derived thyroid carcinoma from 1990 to 2010 displayed that involvement of metastatic pleural effusion was identified as a poor and an unfavorable prognostic factor in these patients [ 44 ]. The previously reported cases of similar presentation of metastatic pleural effusion, either secondary to primary PTC [ 31 , 32 ], or anaplastic transformation of a well-differentiated PTC [ 33 ] are very limited worldwide and mostly were detected in the Japanese population, which demonstrated a similar aggressive course of the disease terminated by patient death.…”
Section: Discussionmentioning
confidence: 99%